Hegel’s Book of Sand, Or on the Beginning of the Beginning and Its Impossibility - Gelžinytė, Brigita (Religija ir kultūra, 2015)
[full article and abstract in Lithuanian; abstract in English] This paper addresses the still-prevailing problem of the beginning in Hegel’s Science of Logic by focusing on the major arguments of Schelling’s critique, which basically laid the foundation for the subsequent reception of Hegel. According to Schelling, Hegel’s concept of the beginning as pure being can only be understood as either a pure tautology or a negative determination, i.e., indicating only the realm of the possible. Contrary to the prevailing strategies, it is argued that the paradox of the beginning, which is present in the Science of Logic, should be maintained instead of resolved. The paper attempts to demonstrate how the dynamic structure of the unity of being and nothing, and the impossibility of (the principle of ) the beginning, appear to be precisely what allow this thinking to proceed and ground the identity of form and content. Thus, by relying on the suggested alternative, which emphasizes the performative aspect of the paradox, the paper seeks to answer Schelling and to bring closer the apparently contradicting positions of both authors.